The Evolved Psychology of Psychedelic Set and Setting: Inferences Regarding the Roles of Shamanism and Entheogenic Ecopsychology - Winkelman, Michael James (Frontiers in Pharmacology, 2021)
This review illustrates the relevance of shamanism and its co-evolution with effects of psilocybin as a framework for identifying evolved aspects of set and setting. Effects of 5HT2 psychedelics on stress adaptation and sociality illustrate adaptive mechanisms through which psychedelics enhanced hominin evolution as environmental factors influencing selection for features our evolved psychology. Shamanic practices employed psychedelics and manipulated extrapharmacological effects through ritual activation of the neuromodulatory systems of serotonin and dopamine and augmenting processes of the reptilian and paleomammalian brains and innate cognitive modules. Evolutionary psychology perspectives on ritual, shamanism and psychedelics shows their roles as exogenous neurotransmitter sources in hominin evolution and their effects in selection for innate dispositions for psychedelic set and setting. Cross-cultural research illustrates shamanism is an empirical phenomenon of foraging societies, with its ancient basis in collective hominid displays, ritual alterations of consciousness, and endogenous healing responses. Differences between chimpanzee maximal displays and shamanic rituals reveal a zone of proximal development in hominin evolution; these are directly related to psychedelic effects and integration of innate modular thought processes. Ritual alterations of consciousness stimulate these and other innate responses such as soul flight and death-and-rebirth experiences. Psychedelic-induced experiences typify a visual symbolism manifesting material from unconscious levels shared with dream processes. Innate modular thought modules (especially self-awareness, other awareness, “mind reading,” spatial and visual intelligence and music) are core features of shamanic universals and recurrent characteristics of psychedelic experience. These are foundations of our evolved set and setting and natural psychology. Psychedelic stimulation and integration of innate cognitive processes is exemplified in animism, animal identities, perceptions of spirits, and psychological incorporation of spirit others. A shamanic-informed psychedelic therapy includes: a preparatory set with practices such as sexual abstinence, fasting and dream incubation; communal ritual settings with singing and dancing; a set derived from innate modular cognitive capacities and their integration expressed in a relational animistic worldview; and spirit relations involving incorporation of animals as personal powers. Psychedelic research and treatment can adopt this shamanic biogenetic paradigm to optimize set, setting and ritual frameworks to enhance psychedelic effects.